The transformer species of the Ukrainian Polissya - Protopopova, Vira V.; Shevera, Myroslav V.; Orlov, Oleksandr O.; Panchenko, Sergiy M. (Biodiversity: Research and Conservation, 2015)
The investigation results of the transformer species participation (Echinocystis lobata (Michx.) Torr. & A. Gray, Heracleum sosnowskyi Manden., Impatiens glandulifera Royle, I. parviflora DC., Reynoutria japonica Houtt., Robinia pseudoacacia L.) in different plant communities of the Ukrainian Polissya (Forest zone of Ukraine) are presented. All the abovementioned species are strong edificators in the region that can significantly change important species composition parameters of communities and character of landscape.